(untitled) (Research, Society and Development, 2022)
The present study aims to identify the sociodemographic profile of users diagnosed with depression in a psychosocial care center (CAPS) in the city of Recife and how these aspects can influence the illness. Thus, this is a descriptive, cross-sectional study of a quantitative approach, where the study sample was collected from secondary data from medical records of users diagnosed with depressive disorder, treated in a CAPS type II disorder, from January to December 2020. Twenty-two medical records were selected according to the inclusion criteria, highlighting the following sociodemographic profile: female users (91.0%), aged between 30 and 39 years (32.0%), single marital status (41.0%) and married (41.0%), full high school (27.0%) and incomplete higher education (27.0%), in the professional condition of employees (59.0%) and monthly income of a minimum wage (45.0%). These variables may be related to mental illness, contributing to depression from psychosocial and biological factors. This study raises the importance of scientific investigation of the relationship between sociodemographic variables and depression, as well as, it will allow strategies and care actions to be outlined by the CAPS team, aimed at improving mental status, expanding the therapeutic perspective specifically to these users.